Building material dry mix comprising a solid vinyl ester resin
Patent Information
- Application Number
- CN202180101143.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-10
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-08-10
AI Technical Summary
这通常花费时间或需要相对强烈的混合和使用助剂,如保护性胶体
[0102]具有本发明的水溶性固体乙烯基酯树脂的应用产品具有出乎意料的性能特性,例如有利的机械强度、特别是高的粘合剂拉伸强度、以及甚至非常高的耐水性。与含有常规保护性胶体的相应建筑产品相比,具有水溶性固体乙烯基酯树脂的建筑产品在热负载之后或在储存之后随着交替冷冻/解冻是更稳定的,并且在水储存之后还具有更小的风化趋势。水溶性固体乙烯基酯树脂可以用于抵消建筑产品中的裂化。有利地,水溶性固体乙烯基酯树脂还值得注意的是高水泥相容性和对矿物建筑材料化合物的高粘附性。
Smart Images

Figure BDA0004689093230000231 
Figure BDA0004689093230000241
Abstract
Description
Technical Field
[0001] This invention relates to dry mixtures of building materials containing solid vinyl ester resins, and to solid vinyl ester resins and methods for preparing such solid vinyl ester resins. It also relates to the use of such dry mixtures of building materials, for example, as adhesives or coating materials, more specifically as tile adhesives, joint fillers, adhesives for thermal insulation composite systems, or as coating materials in the form of self-leveling compounds. Background Technology
[0002] For some time, protective colloidal stabilized polymer powders or dispersions have been used in mineral building material mixtures to equip chemical building products with improved mechanical properties, such as tile adhesives, joint fillers, mortar layers, sealants, or thermal insulation composite systems. This has specifically improved flexural strength, flexibility, and adhesive strength. Protective colloidal stabilized polymers are typically produced through emulsion polymerization or suspension polymerization in an aqueous medium and then converted into redispersible polymer powders by subsequent drying (especially spray drying).
[0003] To further improve the tensile strength of adhesives in building products, protective colloidal stabilized polymers with specific monomer compositions have been recommended, including, for example, trimers based on a good balance of vinyl acetate, vinyl chloride, and ethylene, as described in WO-A2013 / 178721, EP 0334591, and EP-A0255363. For these purposes, EP-A1262465 teaches multi-stage emulsion or suspension polymerization of vinyl esters and (meth)acrylates. For example, polymer blends of vinyl ester copolymers with different glass transition temperatures are also recommended in EP-B12158265, WO-A2006 / 099960, or EP-A702057 for improving the water resistance and / or heat resistance of applied products. EP-A2399955 teaches polymer blends of styrene-butadiene copolymers with different glass transition temperatures. Additives have also been used to control the performance properties of building products. For example, EP-A1238958 recommends zinc oxide, zinc hydroxide, or zinc hydroxide carbonate for delaying the setting of cement mortar compounds without compromising the water resistance of building products.
[0004] Beyond the construction industry, suspensions or emulsions of polymers stabilized with protective colloids or emulsifiers are widely used. For example, WO-A1 2018 / 148929 describes aqueous dispersions of water-insoluble polymers based on olefinically unsaturated silanes, polymerizable anionic emulsifiers, additional olefinically unsaturated monomers, and optionally olefinically unsaturated epoxy compounds as binders for bonding porous polymer materials. US-A1 2002 / 0007009 and EP-A1 2676976 use aqueous dispersions or water-redispersible powders of water-insoluble copolymers having silane and epoxide monomer units in coatings. EP-B13066255 uses such aqueous dispersions of water-insoluble copolymers as binders for textiles.
[0005] Suspension or emulsion polymers are naturally insoluble in water. However, in correspondingly modified dry mixtures of building materials, when these mixtures are combined with water, the polymer powder must be dispersed. This often takes time or requires relatively vigorous mixing and the use of additives, such as protective colloids. Nevertheless, such additives often increase water solubility and can be detrimental to the water resistance of building products.
[0006] As is known, water-redispersible polymer powders are polymer compositions obtained by drying the corresponding polymer aqueous dispersion in the presence of a drying aid. Based on this preparation method, the finely fragmented polymer resin of the dispersion is encapsulated with a conventional water-soluble drying aid. During the drying process, this drying aid acts as a coating, preventing these particles from irreversibly sticking together. When the polymer powder is redispersed in water, the drying aid dissolves, forming an aqueous redispersible body in which the original polymer particles (primary polymer particles) are present again as much as possible (Schulze J. in TIZ, No. 9, 1985).
[0007] In light of this context, there remains a need for building products with improved mechanical strength, and more specifically, improved adhesive tensile strength after water storage, such as tile adhesives, joint fillers, or mortars for insulating composite systems. Furthermore, additives used for these purposes should be readily soluble in water to allow for their timely introduction into water-containing building material mixtures. Summary of the Invention
[0008] The subject of this invention is a dry mixture of building materials comprising one or more hydraulically cured adhesives, one or more fillers, and optionally one or more additives, characterized in that...
[0009] They contain one or more water-soluble solid vinyl ester resins, which can be obtained by solution polymerization or bulk polymerization as follows.
[0010] a) One or more vinyl esters of carboxylic acids having 1 to 20 carbon atoms,
[0011] b) 0.1% to 20% by weight of one or more alkyl-containing unsaturated olefinic monomers (silane monomers), and
[0012] c) 0.5% to 20% by weight of one or more ionic olefinic unsaturated monomers (ionic monomers).
[0013] The figures expressed as a percentage by weight are each based on the total weight of the solid vinyl ester resin.
[0014] Another subject of this invention is a water-soluble solid vinyl ester resin, which can be obtained by solution polymerization or bulk polymerization:
[0015] a) One or more vinyl esters of carboxylic acids having 1 to 20 carbon atoms,
[0016] b) 0.1% to 20% by weight of one or more alkyl-containing unsaturated olefinic monomers (silane monomers), and
[0017] c) 0.5% to 20% by weight of one or more ionic olefinic unsaturated monomers (ionic monomers),
[0018] The figures expressed as a percentage by weight are each based on the total weight of the water-soluble solid vinyl ester resin.
[0019] Water-soluble solid vinyl ester resins are also referred to as solid vinyl ester resins in the following text.
[0020] Solution polymerization and bulk polymerization, and the solid resins obtained thereby, are fundamentally and inherently different from emulsion polymerization and suspension polymerization, and their polymerization products. Emulsion polymerization and suspension polymerization belong to the category of multiphase polymerization and are generally characterized in that the monomers and the polymers formed during polymerization are insoluble in the continuous phase (i.e., in the polymerization medium, typically water), and therefore, for stabilization, polymerization occurs in the presence of emulsifiers or protective colloids, resulting in the migration of these polymer products into micelles, where these polymers form micropolymer coils or latex particles, or polymer beads, or polymer particles, with the emulsifier or protective colloid carried on their surface. In the specific case of emulsion polymerization without emulsifiers, the initiator carries specific groups, typically charged groups, which then form a stable system for multiphase polymerization. In emulsion and suspension polymerization, polar, proton, or ionic monomers and initiators behave similarly to emulsifiers and protective colloids, and therefore, in emulsion or suspension polymers, they are essentially found on the surface of the polymer particles. In contrast, in solution polymerization and bulk polymerization, the monomers and polymers are inherently soluble in the polymerization medium (i.e., the solvent or monomer). Therefore, emulsifiers and protective colloids are typically not used in solution polymerization and bulk polymerization. Due to their solubility in the polymerization medium, these solution polymers exist generally as dissolved polymer chains, unlike emulsions and suspensions which exist as latex particles or polymer particles. Furthermore, in solution and bulk polymers, these distinct monomers (specifically including ionic monomers) are inherently bound to these polymer chains in a uniform distribution, unlike emulsions and suspensions which do not preferentially reside on the surface of polymer particles. Therefore, solution and bulk polymers are inherently structurally different from emulsions or suspensions.
[0021] Suitable vinyl esters a) are those of carboxylic acids having 1 to 20 carbon atoms, more specifically 2 to 15 carbon atoms, such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl 2-ethylhexanoate, vinyl laurate, 1-methyl vinyl acetate, vinyl neopentanoate, and vinyl esters of α-branched monocarboxylic acids having 9 to 11 carbon atoms. Vinyl acetate is particularly preferred.
[0022] Also preferred are combinations of vinyl acetate and one or more other vinyl esters different from vinyl acetate, such as vinyl propionate, vinyl butyrate, vinyl 2-ethylhexanoate, 1-methyl vinyl acetate, and more particularly vinyl laurate, vinyl pentanoate, or vinyl esters of α-branched monocarboxylic acids having 9 to 11 carbon atoms.
[0023] In each case, based on the total weight of the solid vinyl ester resin, the solid vinyl ester resin is based on preferably 60% to 99.4% by weight, more preferably 80% to 98.5% by weight, and most preferably 87% to 97% by weight of vinyl ester (a).
[0024] An example of a silane monomer (b) is the general formula R. 1 SiR 2 0-2 (OR 3 ) 1-3 An unsaturated silicon compound, wherein R1 is defined as CH2=CR 4 -(CH2) 0-1 Or CH2=CR 4 CO2(CH2) 1-3 R 2 The definition is a C1 to C3 alkyl group, a C1 to C3 alkoxy group, or a halogen, preferably C1 or Br, R 3 It is a non-branched or branched optionally substituted alkyl group having 1 to 12 carbon atoms, preferably 1 to 3 carbon atoms, or an acyl group having 2 to 12 carbon atoms, wherein R 3 Optionally interrupted by an ether group, and R 4 It is H or CH3.
[0025] Preferred silane monomers b) are γ-acryloyl- and γ-methacryloyloxypropyltris(alkoxy)silane, α-methacryloyloxymethyltris(alkoxy)silane, γ-methacryloyloxypropyl-methyldi(alkoxy)silane; vinyl silanes such as vinylalkyldi(alkoxy)silane and vinyltris(alkoxy)silane, wherein the alkoxy group used may be, for example, methoxy, ethoxy, methoxyethylene, ethoxyethylene, methoxypropylene glycol ether and / or ethoxypropylene glycol ether group.
[0026] Examples of preferred silane monomers (b) are 3-methacryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropylmethyldimethoxysilane, vinyltrimethoxysilane, vinylmethyldimethoxysilane, vinyltriethoxysilane, vinylmethyldiethoxysilane, vinyldipropoxysilane, vinyltriisopropoxysilane, vinyltri-(1-methoxy)-isopropoxysilane, vinyltert-butoxysilane, vinyltriacetoxysilane, methacryloyloxymethyltrimethoxysilane, 3-methacryloyloxypropyltris(2-methoxyethoxy)silane, vinyltrichlorosilane, vinylmethyldichlorosilane, and vinyltri-(2-methoxyethoxy)silane. Silanes, triacetoxyvinylsilanes, allylvinyltrimethoxysilanes, allyltriacetoxysilanes, vinyldimethylmethoxysilanes, vinyldimethylethoxysilanes, vinylmethyldiacetoxysilanes, vinyldimethylacetoxysilanes, vinylisobutyldimethoxysilanes, vinyltriisopropyloxysilanes, vinyltert-butoxysilanes, vinylethylhexyloxysilanes, vinylmethoxydioxosilanes, vinyltrioctyloxysilanes, vinyldimethoxyoctyloxysilanes, vinyldioctyloxysilanes, vinyldilauryloxysilanes, vinyldimethoxylauryloxysilanes, and polyethylene glycol-modified vinyl silanes.
[0027] The most preferred silane monomers used (b) are vinyltrimethoxysilane, vinylmethyldimethoxysilane, vinyltriethoxysilane, vinylmethyldiethoxysilane, vinyltri(1-methoxy)-isopropoxysilane, methacryloyloxypropyltri(2-methoxyethoxy)silane, 3-methacryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropylmethyldimethoxysilane, and methacryloyloxymethyltrimethoxysilane, as well as mixtures thereof.
[0028] Suitable silane monomers b) are still those with the general formula CH2=CR 5 -CO-NR 6 -R 7 -SiR 8 n-(R 9 ) 3-m (Methacrylamide) containing silyl groups, wherein n = 0 to 4, m = 0 to 2, R 5 It is H or methyl, R 6 It is H or an alkyl group having 1 to 5 carbon atoms; R 7 It is an alkylene group or a divalent organic group having 1 to 5 carbon atoms, wherein the carbon chain is interrupted by O or N atoms, R 8 It is an alkyl group having 1 to 5 carbon atoms, R 9It is an alkoxy group having 1 to 40 carbon atoms that can be substituted with other heterocycles. Two or more R groups are present. 5 Or R 9 In monomers containing groups, these groups can be the same or different.
[0029] Examples of such (meth)acrylamidoalkylsilanes are as follows: 3-(meth)acrylamidopropyltrimethoxysilane, 3-(meth)acrylamidopropyltriethoxysilane, 3-(meth)acrylamidopropyl(β-methoxyethoxy)silane, 2-(meth)acrylamido-2-methylpropyltrimethoxysilane, 2-(meth)acrylamido-2-methylethyltrimethoxysilane, N-(2-(meth)acrylamido-ethyl)aminopropyltrimethoxysilane, 3-(meth)acrylamidopropylacetoxysilane, 2-(meth)acrylamidoethyltrimethoxysilane, 1-(meth)acrylamidopropyltrimethoxysilane, Aminomethyltrimethoxysilane, 3-(meth)acrylamidopropylmethyldimethoxysilane, 3-(meth)acrylamidopropyldimethylmethoxysilane, 3-(N-methyl(meth)acrylamido)propyltrimethoxysilane, 3-((meth)acrylamidomethoxy)-3-hydroxypropyltrimethoxysilane, 3-((meth)acrylamidomethoxy)propyltrimethoxysilane, N,N-dimethyl-N-trimethoxysilylpropyl-3-(meth)acrylamidopropylammonium chloride and NN-dimethyl-N-trimethoxysilylpropyl-2-(meth)acrylamido-2-methylpropylammonium chloride.
[0030] Generally, vinylsilanes are preferred, in other words, silanes containing vinyl groups.
[0031] In each case, based on the total weight of the solid vinyl ester resin, the solid vinyl ester resin is based on preferably 0.5% to 10% by weight, more preferably 1% to 7% and most preferably 1% to 5% by weight of silane monomer (b).
[0032] In each case, based on the total weight of the solid vinyl ester resin, the solid vinyl ester resin is based on preferably 1% to 10% by weight, more preferably 2% to 6% and most preferably 3% to 5% by weight of ionic monomer (c).
[0033] Ionic monomer c) can be a cationic olefin unsaturated monomer (cationic monomer) or preferably anionic olefin unsaturated monomer (anionic monomer).
[0034] Examples of anionic monomers (c) are olefinically unsaturated monomers that additionally carry, for example, carboxylic acid, sulfonic acid, sulfate, or phosphonic acid groups. Monomers carrying sulfonic acid groups are preferred.
[0035] The olefinic unsaturated carboxylic acid can be, for example, a monocarboxylic acid or a dicarboxylic acid, preferably acrylic acid, methacrylic acid, itaconic acid, fumaric acid, maleic acid, and monoesters and diesters of fumaric and maleic acids, such as diethyl ester and diisopropyl ester. Examples of olefinic unsaturated sulfonic acids are methyl allyl sulfonate, vinyl sulfonic acid, 2-acrylamido-2-methyl-propanesulfonic acid (AMPS), styrene sulfonic acid, (meth)acrylate sulfonyl alkyl ester, itaconic acid sulfonyl alkyl ester, preferably having a C1 to C6 alkyl group in each case, and vinyl sulfonic acid.
[0036] Particularly preferred are methyl allyl sulfonate, 2-acryloylamino-2-methylpropanesulfonic acid (AMPS), styrene sulfonic acid, sulfopropyl acrylate, itaconic acid sulfopropyl ester, and vinyl sulfonic acid.
[0037] The most preferred monomer c) is acrylic acid, methacrylic acid, vinyl sulfonic acid, and methallyl sulfonate.
[0038] Anionic monomers (c) can also be in the form of their salts, such as their alkali metal, alkaline earth metal, or ammonium salts, preferably sodium, potassium, calcium, or ammonium salts.
[0039] Examples of cationic monomers (c) are diallyl diethylammonium chloride (DADEAC), (3-methacryloyloxy)propyltrimethylammonium chloride (MPTAC), (3-methacryloyloxy)ethyltrimethylammonium chloride (METAC), (3-methacrylamido)propyltrimethylammonium chloride (MAPTAC), trimethyl-3-(1-acrylamido-1,1-dimethylpropyl)ammonium chloride, trimethyl-3-(1-acrylamido-1,1-dimethylbutyl)ammonium chloride, dimethacrylamidopropyl-4-trimethylammoniumbutenyl-2-ammonium chloride, (2-acrylamidomethoxy)ethyltrimethylammonium chloride, and especially diallyl dimethylammonium chloride (DADMAC).
[0040] Preferred cationic monomers c) are diallyl dimethyl ammonium chloride (DADMAC), diallyl diethyl ammonium chloride (DADEAC), (3-methacryloyloxy)propyltrimethyl ammonium chloride (MPTAC), (3-methacryloyloxy)ethyltrimethyl ammonium chloride (METAC), and (3-methacryloylamino)propyltrimethyl ammonium chloride (MAPTAC).
[0041] Solid vinyl ester resins may optionally be based on one or more additional olefinically unsaturated monomers other than monomers a) to c), examples of which are olefinically unsaturated monomer d) or auxiliary monomers.
[0042] Monomer d) is preferably selected from the group consisting of (meth)acrylates, vinyl aromatic compounds, alkenes, 1,3-dienes and vinyl halides.
[0043] Suitable monomers from the ester group of acrylic acid or methacrylic acid are, for example, esters of unbranched or branched alcohols having 1 to 15 carbon atoms, such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, n-butyl acrylate, n-butyl methacrylate, and 2-ethylhexyl acrylate.
[0044] Examples of vinyl aromatic compounds are styrene, methylstyrene, and vinyltoluene. Examples of halogenated vinyl compounds are vinyl chloride. Examples of alkenes are ethylene and propylene. Examples of dienes are 1,3-butadiene and isoprene.
[0045] Based on the total weight of the solid vinyl ester resin, the solid vinyl ester resin is preferably based on monomer d) in an amount of 0% to 50%, more preferably 1% to 40%, even more preferably 2% to 30%, and very preferably 5% to 20% by weight. The most preferred solid vinyl ester resin does not contain units of monomer d).
[0046] In addition, one or more olefinically unsaturated auxiliary monomers (e) may optionally be present in the copolymer. Examples of auxiliary monomers (e) are olefinically unsaturated formamides and nitriles, preferably acrylamides and acrylonitriles; diesters of fumaric acid and maleic acid, such as diethyl esters and diisopropyl esters, and maleic anhydride; and acetyl acetoxyethyl acrylate or methacrylate. Auxiliary monomers (e) may also be olefinically unsaturated crosslinking monomers (e) such as pre-crosslinking or post-crosslinking monomers (e). Examples of pre-crosslinking monomers (e) are polyolefinically unsaturated monomers, such as divinyl adipate, diallyl maleate, allyl methacrylate, triallyl isocyanurate, or triallyl cyanurate. Examples of post-crosslinking monomers (e) are monomers having epoxy functional groups, such as glycidyl methacrylate and glycidyl acrylate. Other such monomers include those having hydroxyl groups, such as hydroxyalkyl acrylates and hydroxyalkyl methacrylates, more particularly hydroxyethyl acrylate, hydroxypropyl ester, or hydroxybutyl acrylate. The auxiliary monomer e) is generally different from the monomers a) to d) or a) to c) mentioned above, and in particular also different from the monomer a) mentioned above.
[0047] Based on the total weight of the solid vinyl ester resin, the solid vinyl ester resin is preferably based on the auxiliary monomer (e) at a level of 0% to 20%, more preferably 0.5% to 10%, and very preferably 1% to 5% by weight.
[0048] It is also preferred to have solid vinyl ester resins that do not contain monomer units containing hydroxyl or carboxylic anhydride groups. Particularly preferred are solid vinyl ester resins that do not contain N-hydroxymethyl (meth)acrylamide units. Solid vinyl ester resins are also preferably free of N-(alkoxymethyl)(meth)acrylamide units, such as N-(isobutoxymethyl)acrylamide (IBMA), N-(isobutoxymethyl)methacrylamide (IBMMA), N-(n-butoxymethyl)acrylamide (NBMA), or N-(n-butoxymethyl)methacrylamide (NBMMA). Most preferred solid vinyl ester resins do not contain units of crosslinking monomer (e), and more particularly, do not contain monomer units having epoxy functional groups. Very most preferred solid vinyl ester resins do not contain units of auxiliary monomer (e).
[0049] solid vinyl ester resins The viscosity is preferably 0.1 to 100 mPas, more preferably 0.5 to 50 mPas, and most preferably 1 to 10 mPas (according to DIN 53015). Method: Determination at 20°C using a 4% aqueous solution.
[0050] These solid vinyl ester resins have a water solubility of preferably at least 3%, more preferably at least 5%, very preferably at least 10%, and most preferably at least 15% by weight at 23°C.
[0051] Various monomers a) to c) are preferably randomly or uniformly incorporated into solid vinyl ester resins.
[0052] Solid vinyl ester resin is preferably in the form of a solution in an organic solvent, or more preferably an aqueous solution, or in solid form. The solution is preferably clear, but may also have some turbidity, but is generally not in the form of a dispersion. Thus, a solution having a solid vinyl ester resin content of 20% by weight has a turbidity preferably ≤700 EBC, more preferably ≤600 EBC, even more preferably ≤400 EBC, and most preferably ≤200 EBC (measured at room temperature according to DIN 38404 using a turbidity instrument from Metrisa: Model TA6FS / Model 251, according to the Formazin standard).
[0053] Another subject of the present invention is a method for preparing water-soluble solid vinyl ester resins by the following free radical-initiated solution polymerization or bulk polymerization:
[0054] a) One or more vinyl esters of carboxylic acids having 1 to 20 carbon atoms,
[0055] b) 0.1% to 20% by weight of one or more alkyl-containing unsaturated olefinic monomers (silane monomers), and
[0056] c) 0.5% to 20% by weight of one or more ionic olefinic unsaturated monomers (ionic monomers),
[0057] The figures expressed as a percentage by weight are each based on the total weight of the water-soluble solid vinyl ester resin.
[0058] Solid vinyl ester resins are preferably prepared by solution polymerization.
[0059] Solution polymerization is preferably carried out in one or more organic solvents. Examples of organic solvents are alcohols, especially glycols, polyethylene glycol, or aliphatic alcohols having 1 to 6 carbon atoms; ketones, especially acetone or methyl ethyl ketone; esters, especially methyl acetate, ethyl acetate, propyl acetate, or butyl acetate; or ethers. Preferred organic solvents are methanol, isopropanol, methyl acetate, ethyl acetate, and butyl acetate.
[0060] Solvent mixtures may also be used. The solvent mixture preferably contains one or more organic solvents. Based on the total weight of the solvent mixture, a possible solvent mixture may contain ≤20%, more preferably ≤10%, and very preferably ≤5% water by weight. Most preferably, the solvent mixture is water-free. Most preferably, water is not used or is absent during solution polymerization or bulk polymerization.
[0061] Solution polymerization or bulk polymerization can be initiated using typical combinations of thermally activated initiators or redox initiators. Examples of suitable free radical initiators are oil-soluble initiators such as tert-butylperoxy-2-ethylhexanoate, tert-butylperoxyneopentate, tert-butylperoxyneopentate, benzoyl peroxide, tert-pentylperoxyneopentate, di(2-ethylhexyl)peroxydicarbonate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, and di(4-tert-butylcyclohexyl)peroxydicarbonate. Also suitable are azo initiators, such as azobisisobutyronitrile. These initiators are generally used in amounts from 0.005% to 3.0%, preferably 0.01% to 1.5% by weight, in each case based on the total weight of the monomers used to prepare the vinyl acetate-isopropylene acetate copolymer.
[0062] The temperature during polymerization is preferably between 20°C and 160°C, more preferably between 40°C and 140°C. The polymerization reaction is generally carried out under atmospheric pressure, preferably under reflux.
[0063] To control molecular weight, regulators can be used during polymerization. If regulators are used in the form of chain transfer agents, they are typically used in amounts between 0.01% and 5.0% by weight, based on the monomers to be polymerized, and are metered, for example, separately or as a premix with the reaction components. Examples of such agents are n-dodecyl mercaptan, tert-dodecyl mercaptan, mercaptopropionic acid, methyl mercaptopropionate, isopropanol, and acetaldehyde. Chain transfer agents are preferably not used.
[0064] The polymerization process can also be carried out in the presence of an emulsifier or a protective colloid. The preferred amounts of emulsifier and protective colloid are up to 10% by weight, more specifically 0.1% to 10%, based on the total weight of the monomers. Particularly preferably, polymerization is carried out in the absence of an emulsifier and / or, particularly, in the absence of a protective colloid.
[0065] Solutions and / or solids of solid vinyl ester resins are preferably free of emulsifiers and / or especially free of protective colloids.
[0066] Examples of emulsifiers are anionic, cationic, or nonionic emulsifiers, such as anionic surfactants, more specifically alkyl sulfates, alkyl or alkylaryl ether sulfates, alkyl or alkylaryl sulfonates, sulfosuccinate (mono) esters, or nonionic surfactants such as alkyl polyethylene glycol ethers or alkylaryl polyethylene glycol ethers having 8 to 40 ethylene oxide units. Examples of protective colloids are polyvinyl alcohol; polyvinyl acetal; polyvinylpyrrolidone; water-soluble forms of polysaccharides such as starch (amylose and amylopectin), cellulose and their carboxymethyl, methyl, hydroxyethyl and hydroxypropyl derivatives, dextrin and cyclodextrin; proteins such as casein or caseinate, soy protein, gelatin; lignin sulfonates; synthetic polymers such as poly(meth)acrylic acid, copolymers of (meth)acrylates with carboxyl-functionalized comonomer units, poly(meth)acrylamide, polyvinyl sulfonic acid and their water-soluble copolymers; melamine-formaldehyde sulfonate, naphthalene-formaldehyde sulfonate, styrene-maleic acid and vinyl ether-maleic acid copolymers. More particularly, protective colloids are polyvinyl alcohol, such as partially hydrolyzed polyvinyl alcohol, cellulose ethers such as methyl-, methylhydroxypropyl- and hydroxyethyl-cellulose, and carboxymethyl-cellulose.
[0067] Polymerization can be carried out in a batch manner, where all components are included in the initial reactor feed, or in a metering manner, where one or more components are fed during polymerization. A mixing mode with initial feed and metering is preferred. The metered feed can be prepared separately (in space and time), or some or all of the components used for metering can be metered in after pre-emulsification.
[0068] In the case of solution polymerization, the polymerization reaction is carried out in general to a solids content of 10% to 70% by weight, preferably 15% to 60%.
[0069] At the end of polymerization, residual monomers can be removed by known methods, such as by post-polymerization initiated with a redox catalyst. Volatile residual monomers can also be removed by distillation or stripping, preferably under reduced pressure, and optionally by passing through or over an inert entrainment gas such as air, nitrogen, or vapor in the product.
[0070] To convert polymers into solid vinyl ester resins, their solutions can be dried in conventional ways, such as by distillation to melt, fluidized bed drying, roller drying, freeze drying, or spray drying. Spray drying of the solution is preferred. Particularly preferred is the removal of volatile residual monomers or other volatile components, such as solvents, by distillation, preferably under reduced pressure.
[0071] For example, to improve performance characteristics, solid vinyl ester resins can be blended with adjuvants such as pigments, fillers, anti-sticking agents, redispersible polymer powders, foam stabilizers, or hydrophobic agents.
[0072] A further subject of the invention is polymer compositions comprising one or more protective colloidal or emulsifier-stabilized polymers (base polymers) based on olefinic unsaturated monomers in the form of aqueous dispersions or water-redispersible powders, characterized in that they comprise one or more water-soluble solid vinyl ester resins of the invention.
[0073] Using these types of polymer compositions, the objectives of the present invention can be achieved more effectively; in particular, the mechanical properties of building products can be improved.
[0074] Based on the dry weight of the polymer composition, the polymer composition preferably contains 1% to 80%, more suitablely 5% to 60%, and most preferably 10% to 40% by weight of solid vinyl ester resin.
[0075] Based on the dry weight of the polymer composition, the polymer composition preferably contains 20% to 99%, more preferably 40% to 95%, and most preferably 60% to 90% by weight of a protective colloidal stabilized or emulsifier stabilized base polymer.
[0076] The polymer composition is preferably in the form of an aqueous dispersion or a water-redispersible powder.
[0077] In the polymer composition, the base polymer and the solid vinyl ester resin are preferably in the form of a blend only.
[0078] The base polymers are preferably water-insoluble. These base polymers have a water solubility of preferably up to 1%, more preferably up to 0.9%, by weight at 23°C. The solubility characteristics of the polymers depend, for example, on their monomer composition. Those skilled in the art can provide water-insoluble or water-soluble polymers based on several ranging tests.
[0079] The base polymer is preferably based on one or more monomers from the group consisting of vinyl esters of unbranched or branched carboxylic acids having 1 to 18 carbon atoms, acrylic acid and methacrylic acid and esters of unbranched or branched alcohols having 1 to 18 carbon atoms, vinyl aromatic compounds, vinyl halides and olefins.
[0080] These monomers can be implemented in the preferred and particularly preferred ways described above.
[0081] The base polymer is typically different from the water-soluble copolymer of this invention. The base polymer preferably does not contain silane monomer units (b).
[0082] Based on the total weight of the base polymer, the base polymer is based on the aforementioned monomers a) and d) in a manner that is preferably ≥80%, more preferably ≥90%, even more preferably ≥95%, very preferably ≥98%, even more preferably ≥99%, and most preferably ≥99.5% by weight. Most particularly preferred is that the base polymer is exclusively based on the aforementioned monomers a) and d).
[0083] Examples of suitable base polymers are vinyl acetate homopolymers, copolymers of vinyl acetate and ethylene, copolymers of vinyl acetate and ethylene and one or more other vinyl esters, copolymers of vinyl acetate and ethylene and acrylates, copolymers of vinyl acetate and ethylene and vinyl chloride, styrene-acrylate copolymers, and styrene-1,3-butadiene copolymers.
[0084] Preferred are vinyl acetate homopolymers; copolymers of vinyl acetate with 1% to 40% by weight of ethylene; copolymers of vinyl acetate with: 1% to 40% by weight of ethylene and 1% to 50% by weight of one or more additional comonomers from the group consisting of: vinyl esters having 1 to 12 carbon atoms in the carboxylic acid group, such as vinyl propionate, vinyl laurate, vinyl esters of α-branched carboxylic acids having 5 to 13 carbon atoms, such as VeoVa9R, VeoVa10R, VeoVa11R; vinyl acetate, 1% to 40% by weight of ethylene and preferably 1% to 60% by weight of unbranched or branched alcohols having 1 to 15 carbon atoms (especially n-butyl acrylate or 2-... A copolymer of vinyl acetate (ethylhexyl ester); and a copolymer comprising 30% to 75% by weight vinyl acetate, 1% to 30% by weight vinyl laurate or vinyl ester of α-branched carboxylic acid having 5 to 13 carbon atoms, and 1% to 30% by weight unbranched or branched alcohols of acrylate (especially n-butyl acrylate or 2-ethylhexyl acrylate) having 1 to 15 carbon atoms, the copolymer may also contain 1% to 40% by weight ethylene; a copolymer comprising vinyl acetate, 1% to 40% by weight ethylene, and 1% to 60% by weight vinyl chloride; wherein the polymer may also contain a specified amount of the auxiliary monomer, and wherein the percentage by weight in each case totals 100% by weight.
[0085] Also preferred are (meth)acrylate polymers, such as copolymers of n-butyl acrylate or 2-ethylhexyl acrylate, or copolymers of methyl methacrylate with n-butyl acrylate and / or 2-ethylhexyl acrylate and optionally ethylene; styrene-acrylate copolymers having one or more monomers from the group consisting of methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, and 2-ethylhexyl acrylate; vinyl acetate-acrylate copolymers having one or more monomers from the group consisting of methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate and optionally ethylene; styrene-1,3-butadiene copolymers; wherein the polymer may also contain a specified amount of the auxiliary monomers, and wherein the percentage by weight in each case totals 100% by weight.
[0086] The selection of comonomers and their weight fractions for the base polymer is made to generally result in a glass transition temperature (Tg) of -50°C to +50°C, preferably -30°C to +40°C. The glass transition temperature (Tg) of the polymer can be determined in a known manner by differential scanning calorimetry (DSC). Tg can also be approximately calculated in advance using the Fox equation. According to Fox T.G., Bull. Am. Physics Soc. 1, 3, page 123 (1956): 1 / Tg = x1 / Tg1 + x2 / Tg2 + ... + xn / Tgn, where xn is the mass fraction of monomer n (by weight % / 100), and Tgn is the glass transition temperature of the homopolymer of monomer n in Kelvin. The Tg values for the homopolymer are listed in Polymer Polymer Handbook, 2nd edition, J. Wiley & Sons, New York (1975).
[0087] Typically, the preparation of a base polymer in the form of an aqueous dispersion or water-redispersible powder occurs via free radical polymerization of an olefinic unsaturated monomer, in the presence of a protective colloid and / or emulsifier, through suspension or emulsion polymerization, and optionally with subsequent drying.
[0088] The aforementioned protective colloids and / or emulsifiers can be used. Furthermore, the preparation of the base polymers and their drying can be carried out in a conventional manner, such as as described in DE-A102006007282.
[0089] Dry mixtures of building materials include hydraulically hardened binders; fillers; water-soluble solid vinyl ester resins in the form of water-redispersible powders and optionally one or more protective colloidal or emulsifier-stabilized polymers based on olefinic unsaturated monomers (base polymers); and optional additives.
[0090] Preferably, the water-soluble solid vinyl ester resin and the protective colloid or emulsifier-stabilized polymer (base polymer) based on olefin unsaturated monomers in the form of a premix, i.e., preferably in the form of the polymer composition of the present invention, are introduced into the dry mixture of building materials.
[0091] The dry mixture of building materials preferably contains 0.1% to 50%, more preferably 1% to 20%, and most preferably 3% to 10% by weight of water-soluble solid vinyl ester resin, based on the dry weight of the dry mixture in each case.
[0092] The dry mixture of building materials preferably contains 0.1% to 30%, more preferably 0.3% to 12.0%, and most preferably 0.5% to 5.0% by weight of the polymer composition of the present invention, based on the dry weight of the dry mixture in each case.
[0093] Suitable hydraulic binders include cement, particularly Portland cement, aluminate cement, pozzolanic cement, slag cement, magnesium oxide cement, phosphate cement, or blast furnace cement, as well as blended cement, filler cement, fly ash, silica fume, hydrated lime, and gypsum. Portland cement and slag cement are preferred, along with blended cement, filler cement, hydrated lime, and gypsum, and especially aluminate cement. Combinations of aluminate cement and one or more other hydraulic binders are also preferred.
[0094] Typically, dry building material mixtures contain 5% to 50%, preferably 10% to 30% by weight of a hydrohardening adhesive, in each case based on the dry weight of the dry building material mixture.
[0095] Examples of suitable fillers include quartz sand, quartz powder, calcium carbonate, dolomite, aluminum silicate, clay, chalk, quicklime, talc, or mica, or lightweight fillers such as pumice, foamed glass, aerated concrete, perlite, vermiculite, and carbon nanotubes (CNTs). Any desired mixture of the aforementioned fillers may also be used. Quartz sand, quartz powder, calcium carbonate, chalk, or quicklime are preferred.
[0096] Typically, dry mixtures of building materials contain 30% to 90%, preferably 40% to 85% filler by weight, in each case based on the dry weight of the dry mixture.
[0097] Additives used in dry mixtures of building materials include, for example, thickeners (examples of which are polysaccharides such as cellulose ethers and modified cellulose ethers), starch ethers, guar gum, xanthan gum, pisilicates, polycarboxylic acids such as polyacrylic acid and its esters, and polyvinyl alcohol (which may optionally be acetalized or hydrophobically modified), casein, and associative thickeners. Other common additives are retardants, such as hydroxycarboxylic acids or dicarboxylic acids or their salts, sugars, oxalic acid, succinic acid, tartaric acid, gluconic acid, citric acid, sucrose, glucose, fructose, sorbitol, and pentaerythritol. Accelerators are common additives, examples of which are alkali metal or alkaline earth metal salts of organic or inorganic acids. Other additives include the following: hydrophobic agents, preservatives, film-forming aids, dispersants, foam stabilizers, defoamers, and flame retardants (e.g., aluminum hydroxide).
[0098] Additives are used in their usual amounts, depending on the nature of the adjuvant. In each case, based on the dry weight of the dry mixture of the building materials, these amounts are preferably 0% to 15% by weight, more specifically 0.01% to 10%.
[0099] Dry building material mixtures are typically produced by mixing hydraulically cured adhesives, fillers, water-soluble solid vinyl ester resins and / or polymer compositions, and optional additives. Dry building material mixtures can be produced using standard processes inherent in conventional equipment. The amount of water required to process dry building material mixtures is usually added directly before application.
[0100] Dry building material mixtures are suitable for, for example, producing reinforcing compounds for thermal insulation composite systems or for producing adhesives or coating materials. Examples of adhesives are adhesives for thermal and acoustic insulation panels, tile adhesives, and adhesives for bonding wood and wood-based materials. Examples of coating materials are mortars, leveling compounds, mortar layers, and base coats. Dry building material mixtures are particularly preferred for use as tile adhesives, as joint fillers, or as adhesives for thermal insulation composite systems.
[0101] The water-soluble solid vinyl ester resin and / or the polymer composition of the present invention are also suitable as adhesives in mortars, filler compounds, leveling compounds, renderers, building adhesives or sealants.
[0102] Applications of the water-soluble solid vinyl ester resin of this invention exhibit unexpected performance characteristics, such as advantageous mechanical strength, particularly high adhesive tensile strength, and even very high water resistance. Compared to corresponding building products containing conventional protective colloids, building products with water-soluble solid vinyl ester resins are more stable after heat loading or after storage with alternating freeze / thaw cycles, and also exhibit less weathering tendency after water storage. Water-soluble solid vinyl ester resins can be used to counteract cracking in building products. Advantageously, water-soluble solid vinyl ester resins also demonstrate high cement compatibility and high adhesion to mineral building material compounds.
[0103] Another particularly advantageous feature is the water solubility of the solid vinyl ester resin of the present invention, even without the use of protective colloids or emulsifiers. In this invention, any influence of such stabilizing systems on the viscosity, rheology, or general processing characteristics of fresh mortar, or on the properties of cured building products (such as the tensile strength of wet adhesives), can be eliminated. Therefore, dry mixtures of building materials containing water-soluble solid vinyl ester resins can be prepared quickly and efficiently with water and processed in a conventional and simple manner. Detailed Implementation
[0104] The following examples are used to further illustrate the present invention:
[0105] Preparation of solid resins
[0106] Invention Embodiment 1:
[0107] Solid polyvinyl acetate resin having 5% by weight sulfonate monomers and 2.5% by weight silane monomers:
[0108] 109.5 g of vinyl acetate, 14.8 g of 40% MLSA solution (methylallyl sulfonate), 3.0 g of Geniosil GF56, 0.6 g of TBPPI (tert-butyl peroxypentanoate, 75% solution in aliphatic compounds), and 164.2 g of methanol were loaded into a 2 L stirred glass vessel equipped with an anchor stirrer, reflux condenser, and metering device. The initial feed was heated to 70 °C under nitrogen at 150 rpm. Upon reaching the internal temperature of 70 °C, 620.7 g of vinyl acetate, 16.8 g of Geniosil GF56, 83.9 g of Geropon MLSA solution, and 3.8 g of 75% TBPPI (solution in aliphatic compounds) in 39.5 g of methanol were metered in. The monomer solution was metered in over 240 minutes, and the initiator solution was metered in over 300 minutes. After the initiator feed is completed, polymerization continues at 80°C for 5 hours. Volatile components are removed under reduced pressure.
[0109] The copolymer The viscosity (10% by weight in water at 20°C) is 3.2 mPas.
[0110] Embodiment 2 of the Invention:
[0111] Solid polyvinyl acetate resin having 5% by weight sulfonate monomers and 5% by weight silane monomers:
[0112] 163.4 g of methanol and 0.6 g of TPPPI (tert-butyl peroxypentanoate, 75% solution in aliphatic compound) were charged into a 2 L stirred glass vessel equipped with an anchor stirrer, reflux condenser, and metering device. The initial feed was heated to 70 °C under nitrogen at a stirrer speed of 150 rpm. Upon reaching the internal temperature of 70 °C, 706.8 g of vinyl acetate, 98.2 g of 40% MLSA solution, 39.3 g of Geniosil GF56, and 3.8 g of 75% TPPPI (solution in aliphatic compound) in 39.3 g of methanol were metered in. The monomer solution was metered in over 240 minutes, and the initiator solution was metered in over 300 minutes. After the initiator feed was completed, polymerization continued at 80 °C for 5 hours. Volatile components were removed under reduced pressure.
[0113] The copolymer The viscosity (10% by weight in water at 20°C) is 4.4 mPas.
[0114] Comparative Example 1:
[0115] Solid polyvinyl acetate resin containing 5% by weight of sulfonate monomers but no silane monomers:
[0116] 165.0 g of methanol and 0.6 g of TBPPI (tert-butyl peroxypentanoate, 75% solution in aliphatic compound) were charged into a 2 L stirred glass vessel equipped with an anchor stirrer, reflux condenser, and metering device. The initial feed was heated to 70 °C under nitrogen at a stirrer speed of 150 rpm. Upon reaching the internal temperature of 70 °C, 753.8 g of vinyl acetate, 99.2 g of 40% MLSA solution, and 3.8 g of 75% TBPPI (solution in aliphatic compound) in 39.7 g of methanol were metered in. The monomer solution was metered in over 240 minutes, and the initiator solution was metered in over 300 minutes. After the initiator feed was completed, polymerization continued at 80 °C for 5 hours. Volatile components were removed under reduced pressure.
[0117] The copolymer The viscosity (10% by weight in water at 20°C) is 2.2 mPas.
[0118] Comparative Example 2:
[0119] Solid polyvinyl acetate resin containing 2.5% by weight of silane monomers but without sulfonate monomers:
[0120] 109.5 g of vinyl acetate, 2.8 g of Geniosil GF56, 0.6 g of TBPPI (tert-butyl peroxypentanoate, a 75% solution in an aliphatic compound) and 163.2 g of methanol were charged into a 2 L stirred glass vessel equipped with an anchor stirrer, reflux condenser, and metering device. The initial feed was heated to 70 °C under nitrogen at a stirrer speed of 150 rpm. Upon reaching the internal temperature of 70 °C, 601.2 g of vinyl acetate, 14.6 g of Geniosil GF56, and 3.7 g of 75% TBPPI (a solution in an aliphatic compound) were metered into 39.5 g of methanol. The monomer solution was metered over 240 minutes, and the initiator solution was metered over 300 minutes. After the initiator feed was completed, polymerization continued at 80 °C for 5 hours. Volatile components were removed under reduced pressure.
[0121] The copolymer The viscosity (10% by weight in ethyl acetate at 20°C) is 6.8 mPas.
[0122] Comparative Example 3:
[0123] Hydrolyzed solid polyvinyl acetate resin:
[0124] The solid polyvinyl acetate resin from Example 1 of the invention was hydrolyzed as follows:
[0125] 1403.8 g of a 69.5% methanol resin solution (from the solid polyvinyl acetate resin of Example 1) and 395.3 g of methanol were placed in a 2 L stirred glass container equipped with an anchor stirrer, a reflux condenser, and a metering device. The solution was heated to 30°C and covered with a solution of 7.3 g of 46% sodium hydroxide solution in the 140.3 g methanol. The stirrer was then switched to 200 rpm and hydrolysis was carried out for 2 h.
[0126] During hydrolysis, the copolymer undergoes irreversible gelation, and the gel is no longer completely soluble even when diluted with methanol or water; the gel cannot be used as a water-soluble polymer.
[0127] Water compatibility testing of solid polyvinyl acetate resin:
[0128] Invention Example 1: Dissolved in water to a concentration of at least 20% by weight
[0129] Example 2 of the invention: Dissolved in water to a concentration of at least 20% by weight.
[0130] Testing of solid resin as the sole adhesive:
[0131] The adhesives using each solid resin as a filler from the embodiments of the invention and the comparative examples were tested.
[0132] This was performed by mixing 5% by weight of the relevant solid resin as a 20% by weight aqueous solution with sand, establishing a pH of 9-10, and drying the resulting mixture as a 3 mm thick layer overnight (16 hours) under standard conditions (23°C, 50% relative humidity). Water resistance was then tested, as reported in Table 1.
[0133] Table 1: Adhesives using solid resins as fillers:
[0134]
[0135]
[0136] Compared with the solid resins of Comparative Examples 1 to 3, the solid resin of the present invention stably binds fillers even after water storage.
[0137] Testing for solid resin in tile adhesive:
[0138] Based on the values in Table 2, the cement brick adhesive is produced using the following formula:
[0139] 250g Milke CEM I,
[0140] 100g Fondu Lafarge
[0141] 282g fine quartz sand,
[0142] 332g coarse quartz sand,
[0143] 3.6g Tylose
[0144] 1.0g accelerator,
[0145] 1.4g inhibitor,
[0146] 30g VINNAPAS polymer powder (Wacker Chemie trade name),
[0147] Optionally, 10g of solid resin, as shown in Table 2,
[0148] 200g of water.
[0149] Using these tile adhesive formulations, tile adhesive was routinely produced and applied for the production of tile components. The shear strength of these tile components was tested according to DIN 53265. The test results are summarized in Table 2.
[0150] Table 2: Tests for solid resin in tile adhesive:
[0151] <![CDATA[Dry storage a ) subsequent shear strength (N / mm 2 )]]> 1.87 2.71 1.93 <![CDATA[Wet storage b ) subsequent shear strength (N / mm 2 )]]> 1.51 2.01 1.88
[0152] a) 28d SC: Tested after 28 days of storage under standard conditions;
[0153] b) 7d SC / 21d WS: Tested after 7 days of storage under standard conditions and 21 days of wet storage (in water at 23°C).
[0154] The polymer of this invention improves the adhesive tensile strength of ceramic tile components, particularly in the case of water storage.
Claims
1. A dry mixture of building materials, comprising one or more water-curing adhesives and one or more fillers, characterized in that... The dry mixture contains one or more water-soluble solid vinyl ester resins, which are obtained by solution polymerization or bulk polymerization as follows: a) 60% to 99.4% by weight of one or more vinyl esters of carboxylic acids having 1 to 20 carbon atoms, b) 0.1% to 20% by weight of one or more alkyl-containing unsaturated olefinic monomers, and c) 0.5% to 20% by weight of one or more ionic olefinic unsaturated monomers. The figures expressed as a percentage by weight are each based on the total weight of the solid vinyl ester resin. The water-soluble solid vinyl ester resin wherein the water has a solubility of at least 3% by weight at 23°C.
2. The dry mixture of building materials according to claim 1, characterized in that, Vinyl ester a) constitutes 80% to 98.5% by weight of the total weight of the water-soluble solid vinyl ester resin.
3. The dry mixture of building materials according to any one of the preceding claims, characterized in that, b) One or more silane monomers are of the general formula R 1 SiR 2 0-2 (OR 3 ) 1-3 Unsaturated silicon compounds, Where R 1 The definition is CH2=CR 4 -(CH2) 0-1 Or CH2=CR 4 CO2(CH2) 1-3 R 2 The definition is a C1 to C3 alkyl group, a C1 to C3 alkoxy group, or a halogen, R 3 It is an unbranched or branched substituted or unsubstituted alkyl group having 1 to 12 carbon atoms or an acyl group having 2 to 12 carbon atoms, and R 4 It is H or CH3, and / or One or more silane monomers (b) have the general formula CH2=CR 5 -CO-NR 6 -R 7 -SiR 8 n-(R 9 ) 3-m (Methacrylamide) containing silyl groups, Where n = 0 to 3, m = 0 to 2, R 5 It is H or methyl, R 6 It is H or an alkyl group having 1 to 5 carbon atoms; R 7 It is an alkylene group or a divalent organic group having 1 to 5 carbon atoms, wherein the carbon chain is interrupted by O or N atoms, R 8 It is an alkyl group having 1 to 5 carbon atoms, and R 9 It is an alkoxy group having 1 to 40 carbon atoms, which can be replaced by other heterocycles.
4. The dry mixture of building materials according to claim 1 or 2, characterized in that, b) One or more silane monomers are selected from the group consisting of vinyltrimethoxysilane, vinylmethyldimethoxysilane, vinyltriethoxysilane, vinylmethyldiethoxysilane, methacryloyloxypropyltri(2-methoxyethoxy)silane, 3-methacryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropylmethyldimethoxysilane and methacryloyloxymethyltrimethoxysilane.
5. The dry mixture of building materials according to claim 1 or 2, characterized in that, Ionic monomer c) is another olefinic unsaturated monomer with a carboxylic acid, sulfonic acid, sulfate ester or phosphonic acid group.
6. The dry mixture of building materials according to claim 1 or 2, characterized in that, c) One or more ionic monomers are selected from the group consisting of: acrylic acid, methacrylic acid, itaconic acid, fumaric acid, maleic acid, monoesters and diesters of fumaric acid and maleic acid, methallyl sulfonates, vinyl sulfonic acids, 2-acrylamido-2-methyl-propanesulfonic acid, styrene sulfonic acid, (meth)acrylate sulfonyl alkyl esters, itaconic acid sulfonyl alkyl esters, diallyl diethylammonium chloride, (3-methacryloyloxy)propyltrimethylammonium chloride, (3-methacryloyloxy)ethyltrimethylammonium chloride, (3-methacrylamido)propyltrimethylammonium chloride, trimethyl-3-(1-acrylamido-1,1-dimethylpropyl)ammonium chloride, trimethyl-3-(1-acrylamido-1,1-dimethylbutyl)ammonium chloride, dimethacrylamidopropyl-4-trimethylammonium butenyl-2-ammonium chloride, 2-(acrylamidomethoxy)ethyltrimethylammonium chloride, and diallyl dimethylammonium chloride.
7. The dry mixture of building materials according to claim 1 or 2, characterized in that, Based on the dry weight of the building material dry mixture, the building material dry mixture contains 0.1% to 50% by weight of water-soluble solid vinyl ester resin.
8. A premix comprising a protective colloidal or emulsifier-stabilized polymer based on an olefinically unsaturated monomer in the form of a water-redispersible powder and a water-soluble solid vinyl ester resin, characterized in that, The water-soluble solid vinyl ester resin can be obtained through solution polymerization or bulk polymerization as follows: a) 60% to 99.4% by weight of one or more vinyl esters of carboxylic acids having 1 to 20 carbon atoms, b) 0.1% to 20% by weight of one or more alkyl-containing unsaturated olefinic monomers, and c) 0.5% to 20% by weight of one or more ionic olefinic unsaturated monomers. The figures expressed as a percentage by weight are each based on the total weight of the solid vinyl ester resin. The water-soluble solid vinyl ester resin described herein has a water solubility of at least 3% by weight at 23°C. The protective colloidal stabilized polymers based on olefin unsaturated monomers and the emulsifier stabilized polymers based on olefin unsaturated monomers are water-insoluble.
9. The dry mixture of building materials according to claim 1, characterized in that, Based on the dry weight of the building material dry mixture, the building material dry mixture contains 0.15% to 55% by weight of the premix according to claim 8.
10. Use of the dry mixture of building materials according to any one of claims 1-7 and 9, as a reinforcing compound for thermal insulation composite systems, or as an adhesive for thermal insulation boards, sound insulation boards, tile adhesives, or as an adhesive for bonding wood or wood materials, or as a coating material.
Citation Information
Patent Citations
Process for the preparation of cationically stabilized and water-redispersible polymer powder compositions
DE102006007282A1
Terpolymer emulsions
EP0255363A2
Modified terpolymer emulsions
EP0334591A1
Heterogenous polyvinylester dispersions and powders
EP0702057A2
Dry mortar having improved processing properties
EP1238958A1